Categories for Highly Abstract Ontologies: Limitations & Recommendations (Advances in Knowledge Representation, 2025)
What’s in a name? This paper highlights some limitations of existing category terms for highly abstract ontologies (and similar types of abstraction models), and proposes recommendations. It thereby contributes to research into terminology, conceptual analysis, conceptual modeling, ontology, foundational ontology development, and knowledge representation.